2021
DOI: 10.3390/ph14070693
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Human Carbonic Anhydrase I, II, IX, and XII Inhibition Studies of Sulphonamides Incorporating Mono-, Bi- and Tricyclic Imide Moieties

Abstract: New derivatives were synthesised by reaction of amino-containing aromatic sulphonamides with mono-, bi-, and tricyclic anhydrides. These sulphonamides were investigated as human carbonic anhydrases (hCAs, EC 4.2.1.1) I, II, IX, and XII inhibitors. hCA I was inhibited with inhibition constants (Kis) ranging from 49 to >10,000 nM. The physiologically dominant hCA II was significantly inhibited by most of the sulphonamide with the Kis ranging between 2.4 and 4515 nM. hCA IX and hCA XII were inhibited by these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Compound 123 also showed a value of 20% against maximal electroshock (MES)-induced seizure in animals without epileptic crises (Iman et al, 2018). Davood et al therapeutic targets in various diseases, including epilepsy (Ciccone et al, 2021;Mishra et al, 2020;Thiry et al, 2007) In a recent study, Sethi et al (2021) synthesized and evaluated a series of sulfonamide-based analogs containing phthalimide moieties (126-136) (Figure 10) for their inhibitory activity against four different hCA enzymes (hCAI, hCAII, hCAIX, and hCAXII). The results showed that compounds 126-132 and 134-136 exhibited potent K i values in the range of 0.159-0.463 µM against hCAI, while phthalimides 127-132 and 134-136 showed strong inhibition against hCAII with K i values ranging from 0.0024 to 0.044 µM.…”
Section: Antiepileptic Activitymentioning
confidence: 99%
“…Compound 123 also showed a value of 20% against maximal electroshock (MES)-induced seizure in animals without epileptic crises (Iman et al, 2018). Davood et al therapeutic targets in various diseases, including epilepsy (Ciccone et al, 2021;Mishra et al, 2020;Thiry et al, 2007) In a recent study, Sethi et al (2021) synthesized and evaluated a series of sulfonamide-based analogs containing phthalimide moieties (126-136) (Figure 10) for their inhibitory activity against four different hCA enzymes (hCAI, hCAII, hCAIX, and hCAXII). The results showed that compounds 126-132 and 134-136 exhibited potent K i values in the range of 0.159-0.463 µM against hCAI, while phthalimides 127-132 and 134-136 showed strong inhibition against hCAII with K i values ranging from 0.0024 to 0.044 µM.…”
Section: Antiepileptic Activitymentioning
confidence: 99%
“…In addition, many studies brought to the literature in recent years have emphasized the strong CA inhibitory activity of this group. [ 15–24 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies brought to the literature in recent years have emphasized the strong CA inhibitory activity of this group. [15][16][17][18][19][20][21][22][23][24] Bioisosterism represents one approach used by the medicinal chemist for the rational modification of lead compounds into safer and more clinically effective agents. [25] In the context of contemporary medicinal chemistry and drug discovery, and particularly during lead optimization, isosterism and bioisosterism have been very active areas of research as their principles are directly applicable to structure optimization efforts.…”
mentioning
confidence: 99%
“…Thus, the treatment options have genuinely focused on the amelioration of the cholinergic pathway, and for this purpose, AChE inhibitors were discovered 23 . AChE has recently become a widely used target to improve symptoms of AD 24–26 …”
Section: Introductionmentioning
confidence: 99%
“…23 AChE has recently become a widely used target to improve symptoms of AD. [24][25][26] In this study, the effects of 2-amino thiazole derivatives (Figure 1) on hCA I, hCA II isozymes, AChE and BChE enzyme activities were investigated, their selectivity rates were determined, and inhibition mechanisms were estimated by molecular docking studies.…”
Section: Introductionmentioning
confidence: 99%